HUBUNGAN OBESITAS DENGAN FUNGSI PARU PADA PEMERIKSAAN SPIROMETRI MAHASISWA PROGRAM STUDI PENDIDIKAN DOKTER FAKULTAS KEDOKTERAN UNIVERSITAS ANDALAS - Octavia, Fatharani Nabila; Anggraini, Fika Tri; Yetti, Husna; Irramah, Miftah; Ermayanti, Sabrina; Hanum, Fathiya Juwita (SINERGI : Jurnal Riset Ilmiah, 2025)
Background: Abnormal fat accumulation affects the compliance of the respiratory system which contributes to the process of normal lung expansion. Lung function can be evaluated through an examination using spirometry with the parameters assessed, namely FVC, FEV1, and FEV1/FVC. This study aims to determine the relationship between obesity and lungfunction in the spirometry examination of Andalas University Medical Education students. Methods: This study is an observational analytic study with a cross-sectional approach. The Number of samples in this study was 34 subjects. The sampling technique used wasconsecutive sampling from students of Medical Education at the Faculty of Medicine, AndalasUniversity, Class of 2018-2020. Evaluation of lung function was carried out using aspirometry examination with parameters assessed for FVC, FEV1, and FEV1/FVC while the evaluation of obesity was carried out using the BMI with a classification according toKemenkes RI. Data analysis was carried out using univariate and bivariate qualitative methods. Results: In this study, the majority of respondents were women (70.6%) with normal nutritional status (67.6%) followed by obesity (32.4%). The relationship between obesity and lung function was tested using fisher's exact test. The results showed that there was no relationship between obesity and lung function parameters FVC, FEV1, and FEV1/FVC on spirometry tests.